Istantanea sulla svolta politica di Benjamin verso il Marxismo - Distaso, Leonardo V. (Bollettino Filosofico, 2025)
The essay examines some moments of Benjamin’s theoretical and political turn toward Marxism by catching some aspects of his early position within Western Marxism. The focus is from his meeting with Asja Lācis and his trip to Moscow to the time before his dialogue with Brecht, the phase referred to here as pre-Brechtian. Benjamin’s reflections on the construction of a proletarian culture and literature are connected with the theme of the heritage of bourgeois culture and literature in the transition from the phase of wartime communism to that of the stabilization of the NEP, and the consequences of this on the German cultural milieu. Thus, the first traits of what can be called Benjaminian Marxism become evident. Keywords: Function of Art, Intellectual, Political Theater, Proletarian Literature, Western Marxism